Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Director of Development Carol Bergmann, Dean Mary Kay Kane, and Judge Annette LaRue Luncheon held at the Downtown Club